Development of a Passive Back-Support Exoskeleton Mimicking Human Spine Motion for Multi-Posture Assistance in Occupational Tasks - Jiyuan Wu; Zhiquan Chen; Yinglong Zhang; Qi Zhang; Xingsong Wang; Mengqian Tian (Biomimetics)
Passive back-support exoskeletons commonly employ elastic components to assist users during dynamic tasks. However, these designs are ineffective in providing sustained assistance for prolonged static bending postures, such as those required in surgery, assembly, and farming, where users experience continuous lumbar flexion. To address this limitation, a novel passive back-support exoskeleton inspired by the human spine is proposed in this work. The exoskeleton integrates a five-bar linkage mechanism with vertebrae-mimicking units, allowing for both dynamic flexion–extension movements and rigid support at various flexion angles. During the experiments, subjects are instructed to perform a 30-min forward-bending assembly task under two conditions: with and without wearing the exoskeleton. Compared to the free condition, the electromyography results indicate a 10.1% reduction in integrated EMG (IEMG) and a 9.78% decrease in root mean square (RMS) values of the erector spinae with the exoskeleton. Meanwhile, the metabolic rate is decreased by 11.1%, highlighting the effectiveness of the exoskeleton in mitigating muscle fatigue during prolonged static work. This work provides a promising solution for reducing musculoskeletal strain in occupations requiring sustained forward bending, making it a valuable advancement in passive exoskeleton technology.